Guidelines for landscape and visual impact assessment - Landscape Institute; Institute of Environmental Management and Assessment (London : Routledge, 2013)
'The essential guide to landscape and visual impact assessments for landscape architects from the Landscape Institute and the Institute of Environmental Management and Assessment'--
'Second edition published 2002 by Taylor & Francis'--Title page verso.
Includes bibliographical references and index.
Keywords: Landscape assessment; Landscape protection; Environmental impact analysis